Application of Cultural Philosophy in Holistic Education in Improving Students' Cognitive, Moral and Spiritual - Paramita, Shanti; Suastra, Wayan; Atmaja, Ananta Wikrama Tungga; Tika, I Nyoman (JUPE : Jurnal Pendidikan Mandala, 2024)
Holistic education based on cultural philosophy offers a comprehensive approach to developing students, covering cognitive, moral, and spiritual aspects. This article discusses the application of Tri Hita Karana (THK) as an example of cultural philosophy in the education system. The method used is a Systematic Literature Review (SLR) by analyzing journals or current research related to applying cultural philosophy to improve students' cognitive, moral, and spiritual aspects. Previous research shows that applying THK values can improve students' academic understanding, form responsible, respectful characters, and successfully instill spirituality and ecological awareness. The article also discusses practical implications for curriculum and educator training. Local wisdom-based curriculum, teacher training, and school collaboration with local communities are key to ensuring successful implementation, with an emphasis on mastering contextual learning methods. The THK approach can create a generation that is not only intellectually intelligent but also has a strong moral character and deep spiritual awareness.